Implementation of Legal Aid for the Poor Communities of DKI Jakarta Based on Law No.16 of 2011 (Case Study: Handling Domestic Violence for Women & Children by LKBH FH UPNVJ) - Rahmat, Aulia Annisa; Fatkhuri, Fatkhuri (Dinasti Research, 2024)
The main objective of this research is to discuss how to implement legal aid policies, namely Law no. 16 of 2011, for poor communities, especially for victims of domestic violence in DKI Jakarta. Focuses on interactions and strategies between the National Legal Development Agency, the DKI Jakarta Regional Office of the Ministry of Law & Human Rights, and the FH UPNVJ Legal Assistance and Consultation Institute, as well as identifying problems that arise in providing legal assistance in the field. This research uses the Policy Capacity theory by Xun Wu, M. Ramesh, and M. Howlett. Providing legal assistance by government and non-government actors is faced with many complex challenges, especially handling domestic violence cases in DKI Jakarta, so innovation is needed from actors to overcome these challenges.